Uma análise crítica do papel da jurisprudência no planejamento tributário: tensões principiológicas e desafios à uniformidade - Fortes, Cylmar Pitelli Teixeira (2015)
As in other countries with civil Law tradition, Brazilian legal system incorporates the Law as the primary source and the guarantee of the Rule of Law. Hermeneutics, as the scientific theory of the art of interpretation, imposes itself in our system as the channel destined to compensate the vagueness and imprecision of the law, and resolve the normative conflicts, via the traditional methods and criteria. Jurisprudence, understood as a uniform and constant set of decisions concerning similar subjects, has a secondary role, and the ideas regarding Rights and Justice, in this context, are very close to Law. With the enactment of the 1988´s Democratic Constitution and the rebirth of Brazilian constitutional law, whose philosophical landmark is post-positivism, the Constituent brought regulation to the constitutional principles. However, it did not systemize the relations of the principles between themselves and with the equally positive-like rules of the Constitution; it generated certain principle-logical tensions, as well as among principles and constitutional rules. After surpassing the positive-like pattern, which matched Rights to Law, the discussions related to the neutrality of the regulation´s applicator, and the volunteered and customized actions practiced following subjective ideals of justice were highlighted. In this new context, Jurisprudence takes the role of the main character, and gets the jurisdiction´s Brazilian model closer to common law. However, the extraordinary link of the arbiters to precedents, which comes from the free convincing regime, indicates lack of uniformity and coherence of those that are been judged, concerning similar legal issues, jeopardising stability, generating legal uncertainty and insecurity, and consequently, high obstacles to entrepreneurial planning and the investments that depend on them, what tends to harm the country´s business environment. This perspective´s objective is indicating that Law, as the harmonic system of regulations, requires clear limits, and that these limits, in our constitutional system precisely represent the imposition of methods that guarantee uniform and coherent statements to the Society from the part of the regulation´s applicator, by observing the precedents adequately balanced in terms of harmony, legal security and predictability.